Identification of the binding site on 5S rRNA for the transcription factor IIIA: proposed structure of a common binding site on 5S rRNA and on the gene. - Huber, P W (1986)
Transcription factor IIIA interacts specifically with an internal control region of Xenopus 5S ribosomal RNA genes and is also a component, along with 5S rRNA, of a 7S ribonucleoprotein particle present in previtellogenic oocytes. We have determined the region of the 5S rRNA in the 7S ribonucleoprotein complex that is protected by the transcription factor from digestion with the ribonuclease alpha-sarcin. The binding site for factor IIIA extends from nucleotide 64 through nucleotide 116; the protected region includes two CCUGG helices separated by 11 nucleotides. The same helices occur in the factor IIIA binding site in the 5S rRNA gene and may constitute a common structural feature recognized by the protein in the gene and in the gene product.